2018
DOI: 10.1007/s10461-018-2133-2
|View full text |Cite
|
Sign up to set email alerts
|

But Everyone is Doing It (Sort of)! Perceived Sexual Risks in the Social Environment and the Impact on Homeless Youth Engagement in Concurrent Sexual Relationships

Abstract: Although homeless youth are likely to engage in concurrent sexual relationships and doing so can accelerate HIV transmission, the issue of sexual concurrency (i.e., having sexual partnerships that overlap in time) has received scarce attention in this vulnerable population. The literature that exists tends to focus on individuals' characteristics that may be associated with concurrency and overlooks the influence of their social environment. Informed by the risk amplification and abatement model (RAAM), this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
4
1
Order By: Relevance
“…This higher rate of substance use was subsequently associated with increased experiences of homelessness 1-year posttreatment. While prior studies have posited that homelessness experiences should increase both posttraumatic stress and substance use (Hsu et al, 2018; Radu, 2017; Rice et al, 2005; Tyler et al, 2008; Whitbeck et al, 2007; Yoshioka-Maxwell & Rice, 2017), our results provide a more nuanced cascade of events in which homeless experiences are linked to posttraumatic stress and, subsequently, increased substance use. Theoretically, a symptom-driven perspective may aid in understanding what is happening at the individual level.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This higher rate of substance use was subsequently associated with increased experiences of homelessness 1-year posttreatment. While prior studies have posited that homelessness experiences should increase both posttraumatic stress and substance use (Hsu et al, 2018; Radu, 2017; Rice et al, 2005; Tyler et al, 2008; Whitbeck et al, 2007; Yoshioka-Maxwell & Rice, 2017), our results provide a more nuanced cascade of events in which homeless experiences are linked to posttraumatic stress and, subsequently, increased substance use. Theoretically, a symptom-driven perspective may aid in understanding what is happening at the individual level.…”
Section: Discussioncontrasting
confidence: 53%
“…For example, early work has found that a large majority of homeless and runaway youth have experienced abuse by a parent or adult caretaker (Whitbeck, Hoyt, & Ackley, 1997). Others have found that youth with more experiences of victimization report more time homeless, more substance use and more posttraumatic stress relative to those youth who experience less victimization (Hsu et al, 2018; Radu, 2017; Rice, Milburn, Rotheram-Borus, Mallett, & Rosenthal, 2005; Whitbeck, Hoyt, Johnson, & Chen, 2007; Whitbeck et al, 1999; Yoshioka-Maxwell & Rice, 2017). Prior studies have found that many homeless youth were abused before the age of four, and generally have higher rates of child abuse and neglect than the general population (McManus & Thompson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al found that 44% of children and adolescents who lived on the street had sexual intercourse before they were 14. 21 This study found that more than half of the subjects had sexual intercourse with their partner for the first time for mutual love; more than 90% of the subjects only had one sexual partner, and almost all were female. More studies are needed to evaluate whether knowledge about the modes of transmission of STIs and HIV-related diseases will prevent risky sexual behavior.…”
Section: Discussionmentioning
confidence: 74%
“…Poor reproductive health knowledge was reported in senior high school and junior high school students in Lampung and Central Java Province. 20,21 Indrasari et al reported in Primary Health Care in Samarinda that low sexual knowledge was correlated with high-risk sexual behavior among homosexuals. 20 These data are essential, as sexual health literacy might prevent STIs in street children.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the probability of contracting the Human Immunodeficiency Virus (HIV) and other Sexually Transmitted Diseases (STDs) is more significant among street children, mainly due to unprotected sex and substance abuse (Boyer et al, 2017). The prevalence of HIV among people living on the street in the U.S. is estimated to be two to ten times higher than among young people with stable homes because of unprotected sex with many partners and substance abuse (Hsu et al, 2018). Despite the literature abroad showing an increase in the prevalence of high-risk behavior, such as substance abuse and unsafe sexual behavior among street children, Nepal demonstrates inadequate studies in this area.…”
Section: Problem Statementmentioning
confidence: 99%